Actor Networks and Environmental Conflicts: The Case of Benoa Bay Reclamation (2014-2019) - I Gusti Ngurah Krisna Dana (Universitas Warmadewa, 2024)
This study explores the formation of actor networks in developing conservation areas, specifically focusing on the Benoa Bay conservation area in Bali from 2014 to 2019. This period marks the beginning and temporary cessation of reclamation development permits in the area, instigated by a Presidential Decree. The study examines how actor networks form through material negotiations, categorizing actors into pros (supporting reclamation) and cons (opposing reclamation). It employs the Actor Network Theory (ANT) framework, particularly the moments concept developed by Callon, to analyze these networks and negotiations. The research is qualitative, using case studies and field data collected through interviews with relevant stakeholders. The primary findings reveal that actors on both sides—pro and con—form networks based on the material narratives they promote. For the pros, the need for tourism space justifies reclamation, while the cons focus on conservation values upheld by the Balinese community. The reclamation issue acts as a moment of problematization, bringing these opposing material narratives into conflict within the conservation area. The study follows ANT’s stages from problematization to mobilization, highlighting how the conflicting material narratives of both pro and con actors interact and influence the network formation. Ultimately, the research illustrates the dynamics of actor networks in the context of reclamation, showing how material negotiations shape these networks and the contestation over spatial production in Benoa Bay networks.